IN VIVO ACUTE TOXICITY OF ALOIN EXTRACT ON MALE WHITE MICE (Mus musculus) - Vani, Ade Teti; Putri, Amalia Rahma; Abdullah, Dessy Abdullah; Dewi, Nadia Purnama; Triansyah, Irwan (MSJ : Majority Science Journal, 2024)
Aloin has many benefits potential as a medicine. However, it is necessary to carry out toxicity tests on experimental animals as a pre-screening test. Toxic effect parameters were seen from changes in body weight, tremors, convulsions, salivation, weakness, walking backward, walking on the stomach, death, and levels of SGOT and SGPT in experimental animals. This study aims to evaluate the in vivo acute aloin toxicity test results in mice (Mus Musculus) regarding potential toxic symptoms and animal death. A sample of 27 mice were separated into three groups for this investigation: the control group, the treatment group I at a dose of 2500 µg/kg BW, and the treatment group II at an amount of 5000 µg/kg BW, and 5 mice in the preliminary test. This study employed a laboratory experimental test method using a pre-post control group design study. Based on observations of experimental animals, it concluded neither the preliminary test nor the toxicity test revealed any toxic signs. Neither the initial test nor the toxicity test resulted in any observed animal fatalities. Before and after aloin administration, changes in body weight were significantly different. Treatment group II, treatment group I, and the control group's SGOT levels were classified from highest to lowest, with subsequent values of 22.4 U/L, 21.9 U/L, and 19.9 U/L. The highest value of 35.7 U/L, 32.1 U/L, and 26.2 U/L in the treatment groups II, I, and the control group was used to rank the SGPT levels. There were no toxic symptoms and no mortality in experimental animals, so it can be concluded that aloin did not cause harmful effects in mice, so it was categorized as a pseudo-lethal dose.